Proposal for rural credit and training project: an innovative approach to finance the poor in productive pursuit - BRAC (© BRAC, 2016)
1. Introduction 2. The proposal 3. Implementation plan 4. Expected outcome and evaluation 5. RCTP organization structure 6. Financial analysis